2022
DOI: 10.1097/hjh.0000000000003087
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary sodium-to-potassium ratio and home blood pressure and ambulatory blood pressure: the Ohasama study

Abstract: Objective: No studies have demonstrated the association between urinary sodium-to-potassium (Na/K) ratio and all out-of-office blood pressure (BP) [home morning and evening BP (self-measured at home), and 24-h, daytime, and night-time ambulatory BP] in the same cohort. We aimed to assess, which type of out-of-office BP is more strongly associated with urinary Na/K ratio in the general population.Methods: This cross-sectional study was conducted in the general population of Ohasama, Japan. Home and ambulatory B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A significant change in BP may be observed when BP information is based on out-of-office BP. The Ohasama study previously reported that the uNa/K was significantly associated with home-or daytime-BP, but not with office BP [11]. A meta-analysis found that daily home BP measurements may improve hypertension control [12].…”
mentioning
confidence: 99%
“…A significant change in BP may be observed when BP information is based on out-of-office BP. The Ohasama study previously reported that the uNa/K was significantly associated with home-or daytime-BP, but not with office BP [11]. A meta-analysis found that daily home BP measurements may improve hypertension control [12].…”
mentioning
confidence: 99%